The world's din listening to records, radio and films in New Zealand, 1880-1940 - Hoar, Peter (Otago University Press, 2018)
"New Zealanders started hearing things in new ways when new audio technologies arrived from overseas in the late 19th century. From the first public demonstration of a phonograph in a Blenheim hall in 1879, people were exposed to a succession of machines that captured, stored and transmitted sounds - through radio, cinema and recordings. In The World's Din, Peter Hoar documents the arrival of the first such talking machines', and their growing place in New Zealanders' public and private lives, through the years of radio to the dawn of television. In so doing, he chronicles a sonic revolution' in how New Zealanders heard the world. The change was radical, signifying a defining break from the past. Human experience of the world changed forever during the late 19th and early 20th centuries because we learned to capture, store, and transmit sounds and moving images. 'Audio' since then has been a continued refinement of the original innovation, even in the contemporary era of digital sound, with iPods, streaming audio and Spotify. The World's Din is a beautifully written account that will delight music-lovers and technophiles everywhere. Without further ado, it is time to crank the gramophone, or tune the wireless, or open the Jaffa box as the cinema lights dim, and hearken to the richness and variety of listening in New Zealand's past soundscapes."...Publisher's description